2018
DOI: 10.1007/s00467-018-4103-3
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Recurrence of nephrotic syndrome following kidney transplantation is associated with initial native kidney biopsy findings

Abstract: The original version of this article unfortunately contained a mistake. The subtitle BA Midwest Pediatric Nephrology Consortium (MWPNC) study^was missing. The correct title including subtitle is given above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Our observation is in line with previous studies that report no or very low relapse rate after transplantation in children with genetic SRNS [9,17,19]. Few old reports have suggested a risk of relapse for genetic SRNS, but they are almost all related to NPHS2 mutation, including heterozygous individuals [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our observation is in line with previous studies that report no or very low relapse rate after transplantation in children with genetic SRNS [9,17,19]. Few old reports have suggested a risk of relapse for genetic SRNS, but they are almost all related to NPHS2 mutation, including heterozygous individuals [20][21][22][23].…”
Section: Discussionsupporting
confidence: 92%
“…Nehus et al reported a higher rate of recurrence in younger children, among a cohort of 327 patients, though genetic results were not reported for any participants [24]. No significant difference in relapse rate according to the age at transplant were detected by Tejani and Stablein [12] and in the more recent studies by Ding et al and Pelletier et al [17,19]. Again, unavailability of genetic testing for the majority of their patients could justify the different findings.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 10 Moreover, initial steroid sensitivity has been associated with a higher rate of PTx-REC compared with primary steroid-resistant patients. 11 , 12 …”
mentioning
confidence: 99%